REDESAIN LOGO DAN PERANCANGAN CORPORATE IDENTITY PERUSAHAAN MANUFAKTUR SEPATU SANDAL EKA PROMA SEBAGAI UPAYA MENINGKATKAN KERJASAMA ANTAR PERUSAHAAN - Tyas, Dwi Estining; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal ArtNouveau, 2014)
Redesign logo and corporate identity design of the Proma Eka is an effort to highlight the potential of Eka Proma, by strengthening the brand image that the company is increasingly recognized and can convince big companies to make Eka Proma as his business partner in the contract that bound cooperation .The study was conducted by qualitative research method is to take the interview, observation, documentation, and literature to obtain data that is used as the manufacturers support design concepts. The process of redesigning the logo and corporate identity design refers to the concept of